2012
DOI: 10.1002/hyp.9540
|View full text |Cite
|
Sign up to set email alerts
|

Land use change in a 200‐year period and its effect on blue and green water flow in two Slovenian Mediterranean catchments—lessons for the future

Abstract: The overexploitation and impairment of our freshwater resources require land management strategies that support the preservation of green and blue water flow and various ecosystem services. Historical landscape analysis and the influential driving factors of landscape development provide an essential basis for tackling current environmental questions in land and water management. Hence, this article investigates the influence of historical land use pattern on the hydrological processes and provision of blue an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…The study adds to the demonstrations of the utility in assessing historical catchment conditions to inform current management questions and choices (see also Glavan et al 2012Glavan et al , 2013Tomscha et al 2016). Maps of historic and present-day habitats and ESs themselves provide a means to engage and inform land managers and other stakeholders, and furthermore, the visualisations they provide may contribute to instilling more holistic (i.e., whole catchment) management approaches.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The study adds to the demonstrations of the utility in assessing historical catchment conditions to inform current management questions and choices (see also Glavan et al 2012Glavan et al , 2013Tomscha et al 2016). Maps of historic and present-day habitats and ESs themselves provide a means to engage and inform land managers and other stakeholders, and furthermore, the visualisations they provide may contribute to instilling more holistic (i.e., whole catchment) management approaches.…”
Section: Discussionmentioning
confidence: 94%
“…This includes map-based approaches whereby spatially explicit data on land use, land cover or habitats are the proxies on which supply estimates are based (Burkhard et al 2012;Andrew et al 2015;Science For Environment Policy 2015;Metzger et al 2006;Glavan et al 2013;Syrbe & Walz 2012;Maes et al 2013;Vermaat et al 2015). Maps of different ESs can be produced and compared for the same landscape; however, to date, this approach has been focussed almost entirely on contemporary landscapes and their delivery of different ESs, whereas methodologies for assessing ES changes over time are much more limited (Glavan et al 2012;Haines-Young et al 2012;Tomscha et al 2016). In this study, it is argued that this is actually an important gap in understanding the ES potential of catchments.…”
Section: Introductionmentioning
confidence: 99%
“…Rodrigues, et al [29] also considered the issues of water scarcity, both for blue and green water. Erol and Randhir [30] and Glavan, et al [31] studied the impact of different land use on the availability of freshwater as surface water and groundwater.…”
Section: Water Availability Related Freshwater Ecosystem Servicesmentioning
confidence: 99%
“…The results have shown that there is increasing rate for sediment yield and the sensitivity of rainfall-sediment yield relationship to rainfall changes move down by woodland, paddy field and farmland under the same condition of soil texture and terrain slope in the area. [39] assessed impact of two small scale Slovenian watersheds by using historical land use maps from 1787, 1827, 1940, 1984 and 2009 land use map depicting present situation for LUCC. Results showed statistically insignificant for both watersheds the influence of land use change on total and green water quantity, but would have considerable effects on the seasonal flow.…”
Section: Impact Analysis Of Lucc By Swat Modelmentioning
confidence: 99%